Functional analysis of the Nep1-like proteins from Plasmopara viticola. (31st December 2022) - Xiang, Jiang; Cheng, Jianhui; Wei, Lingzhu; Li, Mingshan; Wu, Jiang
ABSTRACT: Necrosis and ethylene-inducing peptide 1 (Nep1) -like proteins (NLP) are secreted by multiple taxonomically unrelated plant pathogens (bacteria, fungi, and oomycete) and are best known for inducing cell death and immune responses in dicotyledonous plants. A group of putative NLP genes from obligate biotrophic oomycete Plasmopara viticola were predicted by RNA-Seq in our previous study, but their activity has not been established. Therefore, we analyzed the P. viticola NLP ( PvNLP ) family and identified seven PvNLP genes. They all belong to type 1 NLP genes and form a P. viticola -specific cluster when compared with other pathogen NLP genes. The expression of PvNLPs was induced during early infection process and the expression patterns could be categorized into two groups. Agrobacterium tumefaciens -mediated transient expression assays revealed that only PvNLP7 was cytotoxic and could induce Phytophthora capsici resistance in Nicotiana benthamiana . Functional analysis showed that PvNLP4, PvNLP5, PvNLP7, and PvNLP10 significantly improved disease resistance of Arabidopsis thaliana to Hyaloperonospora arabidopsidis . Moreover, the four genes caused an inhibition of plant growth which is typically associated with enhanced immunity when over-expressed in Arabidopsis. Further research found that PvNLP7 could activate the expression of defense-related genes and its conserved NPP1 domain was critical for cell death- and immunity-inducing activity. This record of NLP genes from P. viticola showed a functional diversification, laying a foundation for further study on pathogenic mechanism of the devastating pathogen.